The Assay of Factor VIII: C in Heparinized Plasma: A Polybrene Neutralization Method - Cumming, A M; Wensley, R T; Delamore, I W (Thrombosis and Haemostasis, 1986)
Factor VIII coagulant activity (VIII: C) has been shown by several investigators to exhibit increased stability in vitro when physiological levels of plasma ionized calcium are maintained by anticoagulation with heparin rather than citrate. An increase in initial activity of VIII: C in heparin over that of VIII: C in citrate has been reported but this has not been confirmed. In order to assay VIII :C in heparinized plasma, the heparin anticoagulant effect must be excluded without interfering with the validity of the assay. A one-stage clotting assay for VIII: C has been developed where heparin is neutralized by Polybrene®, a synthetic polymerized quaternary ammonium salt. VIII :C may be accurately measured by this method which satisfies the requirements for a valid assay of parallelism and linearity.
Keywords: VIII:C assay; Heparin neutralization in vitro; Polybrene